GATOR1-related focal cortical dysplasia in epilepsy surgery patients and their families: A possible gradient in severity? - Benova, Barbora; Sanders, Maurits W C B; Uhrova-Meszarosova, Anna; Belohlavkova, Anezka; Hermanovska, Barbora; Novak, Vilem; Stanek, David; Vlckova, Marketa; Zamecnik, Josef; Aronica, Eleonora; Braun, Kees P J; Koeleman, Bobby P C; et al. (European journal of paediatric neurology, 2021)
BACKGROUND: Variants of GATOR1-genes represent a recognised cause of focal cortical dysplasia (FCD), the most common structural aetiology in paediatric drug-resistant focal epilepsy. Reports on familial cases of GATOR1-associated FCD are limited, especially with respect to epilepsy surgery outcomes. METHODS: We present phenotypical manifestations of four unrelated patients with drug-resistant focal epilepsy, FCD and a first-degree relative with epilepsy. All patients underwent targeted gene panel sequencing as a part of the presurgical work up. Literature search was performed to compare our findings to previously published cases. RESULTS: The children (probands) had a more severe phenotype than their parents, including drug-resistant epilepsy and developmental delay, and they failed to achieve seizure freedom post-surgically. All patients had histopathologically confirmed FCD (types IIa, IIb, Ia). In Patient 1 and her affected father, we detected a known pathogenic NPRL2 variant. In patients 2 and 3 and their affected parents, we found novel likely pathogenic germline DEPDC5 variants. In family 4, we detected a novel variant in NPRL3. We identified 15 additional cases who underwent epilepsy surgery for GATOR1-associated FCD, with a positive family history of epilepsy in the literature; in 8/13 tested, the variant was inherited from an asymptomatic parent. CONCLUSION: The presented cases displayed a severity gradient in phenotype with children more severely affected than the parents. Although patients with GATOR1-associated FCD are considered good surgical candidates, post-surgical seizure outcome was poor in our familial cases, suggesting that accurate identification of the epileptogenic zone may be more challenging in this subgroup of patients.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Focal epilepsy; Humans; GTPase-Activating Proteins; proteiny aktivující GTPasu; dítě; malformace mozkové kůry; nádorové supresorové proteiny; Child; Drug Resistant Epilepsy; zárodečné mutace; Female; Targeted gene panel sequencing; Phenotype; lidé; Tumor Suppressor Proteins; Malformations of Cortical Development; refrakterní epilepsie; Epilepsy surgery; Germ-Line Mutation; ženské pohlaví; Male; Retrospective Studies; GATOR1; fenotyp; Adolescent; retrospektivní studie; Malformations of cortical development; mužské pohlaví; Focal cortical dysplasia; mladiství